EFEKTIVITAS PELAKSANAAN QANUN NOMOR 6 TAHUN 2014 TENTANG JINAYAT DI KABUPATEN ACEH UTARA - Mawardi, Mawardi (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Agama Islam Jamiatut Tarbiyah Lhoksukon, 2022)
The enactment of Aceh Qanun Number 6 of 2014 concerning Jinayat is expected to be able to answer the question of the increasing number of jinayah perpetrators in Aceh, especially in North Aceh Regency, but it has been 5 years since the enactment of the Qanun that perpetrators of jinayah in North Aceh Regency are increasing every year, so the expectations the aspirations of the Acehnese people through the Aceh Qanun have not been achieved. The method in this research is empirical juridical which is intended to conduct an assessment of the socialization of jinayat law in Aceh, especially North Aceh and to see the legal reality in society as well as to see the effectiveness of the law in reducing the number of jinayah perpetrators in North Aceh Regency. The results showed that: The socialization of the Jinayat Qanun to the community had been carried out by the Islamic Shari'a Service and the Wilyatul Hisbah, North Aceh Regency, but it was still not perfect, it was only carried out with one method, namely lectures and the media used were also limited, so it did not reach the whole community, then the Qanun Aceh Number 6 of 2014 concerning Jinayah has not been effective in reducing the number of perpetrators of jinayah in North Aceh, this can be seen by the increasing number of criminals every year.